Tightness problems at the flange connection in transient temperature and high pressure condition. (March 2022) - Marek, Piotr; Pawlicki, Jakub; Mościcki, Artur
Highlights: Examination of steam leakages at HP Stage of Turbine. Transient heat transfer analysis of HP Turbine flange connection. Effect of flange bolt prestress reduction by non-steady state (service condition) Impact of thermal expansion and plastic deformation on flange connection tightness. Star-up tests. Experimental validation. Abstract: The main goal of the article is to study, analyze and explain the most apparent cause of transient steam leakage from a high pressure turbine stage body. The analyses focus on transient heat transfer on the metal-metal flange connection of an external turbine casing and start-up tests. The coupled effect of thermal expansions and their impact on the residual bolt pretension force was analyzed in detail using FE models. Series of experiments were performed to confirm the results obtained by numerical calculation. The conclusion provided in this article can be used to improve the design of the flange connection working in variable temperature conditions.